সমাজ ও রাজনৈতিক জীবন-দ্বিতীয় ভাগ, সপ্তম শ্রেণি - (:unkn) unknown (Tripura Board of Secondary Education, 2015)
This book is a Political Science text book for Seventh standard (Class VII) of Tripura Board of Secondary Education.
Samaj O Rajnaitik Jiban, Part 2, Class-VII
Keywords: Bengali; Civics; Bengali; Bengali